LIGHTNER WITMER - THE FATHER OF CLINICAL PSYCHOLOGY - Zarlevski, Kiril (E-Journal VFU, 2026)
The article examines the life and contribution of Lightner Witmer, recognized as the “father of clinical psychology.” From a historical perspective, it analyzes the emergence of clinical psychology, as well as the life and work of its founder, including his training under Wundt and the establishment of the first Psychological Clinic in 1896. The study explores Witmer’s key ideas and concepts, as well as his practical contributions, including the introduction of the term “clinical psychology” and the founding of the journal The Psychological Clinic. The article emphasizes his role in the institutionalization of clinical psychology and its influence on contemporary theory and practice. Special attention is given to Witmer’s enduring legacy and the continued relevance of his ideas.